Dexamethasone Suppressed LPS-Induced Matrix Metalloproteinase and Its Effect on Endothelial Glycocalyx Shedding. (23rd June 2015) - Cui, Na; Wang, Hao; Long, Yun; Su, Longxiang; Liu, Dawei
Abstract : The aim of this study is to determine the mechanism of sepsis-induced vascular hyperpermeability and the beneficial effect of glucocorticoid in protecting vascular endothelium. Male Sprague-Dawley rats were given either a bolus intraperitoneal injection of a nonlethal dose of LPS ( Escherichia coli 055:B5, 10 mg/kg, Sigma) or vehicle (pyrogen-free water). Animals of treatment groups were also given either dexamethasone (4 mg/kg, 30 min prior to LPS injection) or the matrix metalloproteinases (MMPs) inhibitor doxycycline (4 mg/kg, 30 min after LPS injection). Both activities and protein levels of MMP-2 p < 0.001 and MMP-9 p < 0.001 were significantly upregulated in aortic homogenates from LPS-treated rats, associated with decreased ZO-1 p < 0.001 and syndecan-1 p = 0.011 protein contents. Both dexamethasone and doxycycline could significantly inhibit MMPs activity and reserve the expressions of ZO-1 and syndecan-1. The inhibition of MMPs by dexamethasone was significantly lower than that by doxycycline, while the rescue of syndecan-1 expression from LPS-induced endotoxemic rat thoracic aorta was significantly higher in the dexamethasone-treated compared to the doxycycline-treated p = 0.03 . In conclusion, activation of MMPs plays important role in regulating ZO-1 and syndecan-1 protein levels in LPS mediated endothelial perturbation. Both dexamethasone and doxycycline inhibit activation of MMPs that may contribute to the rescue of ZO-1 and syndecan-1 expression.